2016
DOI: 10.3139/146.111425
|View full text |Cite
|
Sign up to set email alerts
|

In-situ annealing and computation study of cube texture development in a commercial aluminum alloy

Abstract: In-situ annealing and computation study of cube texture development in a commercial aluminum alloyThe aim of this study was to identify the physical processes of nucleation and growth of cube grains by means of in-situ annealing experiments. The calculated nucleation site density at cube bands was found not to be sufficient for a correct computational prediction of the cube recrystallization texture. Growth competition at an early stage of recrystallization has to be taken into account for a better agreement b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…2(c)) and mixed texture comprised of a cube recrystallization texture with medium intensities of a retained rolling, or R, texture (Fig. 3(c)) [11][12][13][14]. Accordingly, the interannealed sheet revealed a rather smooth eight-ear profile (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2(c)) and mixed texture comprised of a cube recrystallization texture with medium intensities of a retained rolling, or R, texture (Fig. 3(c)) [11][12][13][14]. Accordingly, the interannealed sheet revealed a rather smooth eight-ear profile (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Such mixed cube + R textures are the typical recrystallization textures of many cold rolled, soft annealed Al alloys (e.g. [11][12][13][14]). Accordingly, the interannealed material showed a very smooth eight-ear profile (Fig.…”
Section: Standard Processing Routementioning
confidence: 99%
“…As expressed in Equation ( 3), the process of nucleation is directly affected by the degree of strain. In the case of the Al alloy deformed with the strain of ~1.38 and annealed at 300 • C, the deformed microstructure contained Cube bands with a length of 34.7 µm, thickness of 3.25 µm, and Cube band spacing of 26.9 µm [54]. This microstructural heterogeneity with the approximate elliptic volume of 1.27 × 10 −14 m 3 tended to produce at least three nuclei at low annealing temperature (T = 300 • C) [54].…”
Section: Modeling the Rx Kineticsmentioning
confidence: 99%
“…In the case of the Al alloy deformed with the strain of ~1.38 and annealed at 300 • C, the deformed microstructure contained Cube bands with a length of 34.7 µm, thickness of 3.25 µm, and Cube band spacing of 26.9 µm [54]. This microstructural heterogeneity with the approximate elliptic volume of 1.27 × 10 −14 m 3 tended to produce at least three nuclei at low annealing temperature (T = 300 • C) [54]. In this case, the total number of nuclei obtained for the incubation period of 1 s is 2.36 × 10 14 m −3 s −1 .…”
Section: Modeling the Rx Kineticsmentioning
confidence: 99%
“…The microscopic mechanism behind the huge advantage of cube grains during recrystallization is still subject to debate, which is summarised in the textbook by Humphreys et al [12]. Recent results from in situ or quasi in situ micro-texture measurements of recrystallization by Albou et al [13] and Sukhopar and Gottstein [14] found cube nuclei at deformed cube bands and in the form of fragments inside differently oriented grains.…”
Section: Introductionmentioning
confidence: 99%